Koumine Suppresses IL-1β Secretion and Attenuates Inflammation Associated With Blocking ROS/NF-κB/NLRP3 Axis in Macrophages - Luo, Yufei; Xiong, Bojun; Liu, Haiping; Chen, Zehong; Huang, Huihui; Yu, Changxi; Yang, Jian (Frontiers in Pharmacology, 2021)
Koumine (KM), one of the primary constituents of Gelsemium elegans, has been used for the treatment of inflammatory diseases such as rheumatoid arthritis, but whether KM impacts the activation of the NOD-like receptor protein 3 (NLRP3) inflammasome remains unknown. This study aimed to explore the inhibitory effect of KM on NLRP3 inflammasome activation and the underlying mechanisms both in vitro using macrophages stimulated with LPS plus ATP, nigericin or monosodium urate (MSU) crystals and in vivo using an MSU-induced peritonitis model. We found that KM dose-dependently inhibited IL-1β secretion in macrophages after NLRP3 inflammasome activators stimulation. Furthermore, KM treatment efficiently attenuated the infiltration of neutrophils and suppressed IL-1β production in mice with MSU-induced peritonitis. These results indicated that KM inhibited NLRP3 inflammasome activation, and consistent with this finding, KM effectively inhibited caspase-1 activation, mature IL-1β secretion, NLRP3 formation and pro-IL-1β expression in LPS-primed macrophages treated with ATP, nigericin or MSU. The mechanistic study showed that, KM exerted a potent inhibitory effect on the NLRP3 priming step, which decreased the phosphorylation of IκBα and p65, the nuclear localization of p65, and the secretion of TNF-α and IL-6. Moreover, the assembly of NLRP3 was also interrupted by KM. KM blocked apoptosis-associated speck-like protein containing a CARD (ASC) speck formation and its oligomerization and hampered the NLRP3-ASC interaction. This suppression was attributed to the ability of KM to inhibit the production of reactive oxygen species (ROS). In support of this finding, the inhibitory effect of KM on ROS production was completely counteracted by H2O2, an ROS promoter. Our results provide the first indication that KM exerts an inhibitory effect on NLRP3 inflammasome activation associated with blocking the ROS/NF-κB/NLRP3 signal axis. KM might have potential clinical application in the treatment of NLRP3 inflammasome-related diseases.